Population policy - Raina, B. L. (Bishen Lal), 1911- (Delhi : B.R. Pub. Corp., 1988)
Evolution of population policies and programs in India.
Includes index.
Bibliography: p. [207]-220.
Keywords: India -- Population policy -- History